Elastyczność strategiczna małych przedsiębiorstw - Ćwik, Krzysztof (Strategic flexibility of small enterprises, 2006)
This paper analyses the problem of organizational flexibility of small enterprises. Special pressure was laid on strategic flexibility. The author compared the results of empirical studies on flexibility of small enterprises with own results apply to small firms' strategies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 82-89